Neuroprotective effects respond to cerebral ischemia without susceptibility to HB-tumorigenesis in VHL heterozygous knockout mice - Wang, Ying (Mol Carcinog, 2017)
The von Hippel-Lindau (VHL) tumor suppressor gene plays a prominent role in the development of hemangioblastomas (HBs) within specific regions of the human’ central nervous system (CNS). Alterations in VHL gene are rarely observed in the more common features of human VHL-related tumors in animal models, and VHL heterozygous knockout (VHL+/−) mice do not develop HBs. We tested whether VHL heterozygous knockout mice exhibited genetic predisposition to the development of HBs and conferred a selective advantage involving growth of blood vessels to its carrier. No differences were observed between wild-type and VHL+/− mice in development ad reproduction. The heterozygous VHL+/− mice did not develop higher genetic susceptibility to CNS-HBs over their lifetime. Furthermore, this recessive VHL gene heterozygosity is relatively stable. Interestingly, we found these heterozygous VHL+/− mice gained an advantage conferring to angiogenic ability in a particular environment, compared with wild type mice. The heterozygous VHL+/− mice obviously enhanced hypoxia inducible factor-1 (HIF)-dependent and Twist1 angiogenic mechanism in response to acute cerebral ischemia, resulting in decreased cerebral tissue damage and neuroprotective response through neovascularization. Our findings provide evidence of partial loss function of VHL as a novel precise therapeutic target in acute cerebral ischemia.